Immunosuppressive Microenvironment in Neuroblastoma - Pistoia, Vito; Morandi, Fabio; Bianchi, Giovanna; Pezzolo, Annalisa; Prigione, Ignazia; Raffaghello, Lizzia (Frontiers in Oncology, 2013)
According to the cancer immunoediting model, the interplay between tumor cells and the host immune system is crucial for the control of tumor growth. NB is a pediatric tumor that presents with metastatic disease at diagnosis in about 50% of the cases, the majority of which have poor prognosis. In this Review article, immune escape pathways adopted by human neuroblastoma (NB) cells are reviewed. These include intrinsic defects of tumor cells such impaired expression of the HLA class I related antigen processing machinery and functional alterations of the tumor microenvironment induced by NB cell-derived immunosuppressive molecules as MICA and HLA-G. Finally, examples of therapeutic interventions targeting the tumor microenvironment are discussed to emphasize the concept that successful cancer treatment may be achieved using this strategy.